PISTON LUBRICATION IN RECIPROCATING COMPRESSORS - Prata, A. T.; Fernandes, J. R. S.; Fagotti, F. (Revista de Engenharia Térmica, 2001)
Piston dynamics plays a fundamental role in two critical processes related to fluid flow in reciprocating compressors. The first is the refrigerant leakage through the radial clearance, which may cause considerable loss in the pumping efficiency of the compressor. The second process is the viscous friction associated with the lubricant film in the radial clearance; certainly a significant factor in the compressor energy consumption. In the present contribution a numerical simulation of the piston movement inside the cylinder of a reciprocating compressor is performed. The compressor considered here is a small hermetic compressor employed in domestic refrigerators. For the problem formulation both the axial and the radial piston motion is considered. In operation, the piston moves up and down along the axis of the cylinder, but the radial oscillatory motion in the cylinder bore, despite being usually small, plays a very important role on the compressor performance and reliability. The compromise between sealing of the gas leakage through the piston-cylinder clearance and the friction losses requires a detailed analysis of the oscillatory motion for a good design. The forces acting on the piston are the hydrodynamic force due to the pressure build up in the oil film (lubrication effects), the force due to the connecting rod, the viscous force associated with the relative motion between the piston and oil, and the force exerted by the gas on the top of the piston. All corresponding moments are also included in the problem formulation of the piston dynamics, in order to determine the piston trajectory, velocity and acceleration at each time step. The hydrodynamic force is obtained from the integration of the pressure distribution on the piston skirt, which, in turn, is determined from a finite volume solution of the time dependent equation that governs the oil flow. A Newton-Raphson procedure was employed in solving the equations of the piston dynamics. The results explored the effects of some design parameters and operating conditions on the stability of the piston, its sealing performance and friction losses. Emphasis was placed on investigating the influence of the pin location, radial clearance and oil viscosity on the piston dynamics. The complexity of the piston movement in reciprocating compressors was demonstrated and the detailed model presented can be employed as an useful tool for engineering design.